VET Teachers' Interpretations of Individualisation and Teaching of Skills and Social Order in two Nordic Countries. (May 2019) - Eiríksdóttir, Elsa; Rosvall, Per-Åke
The age at which young people leave education for the labour market has increased in recent decades, and entering upper secondary education has become the norm. As a result, the diversity of the student population has increased, for instance in terms of students' academic merits and achievements at school. Increased diversity seems to affect vocational education and training more than tracks preparing students for higher education, because entry into vocational education and training (VET) programmes is rarely selective. In this article we analyse a series of interviews with VET teachers regarding VET practices in upper secondary schools in Sweden and Iceland. We examine how policy plays out in practice in VET by looking at how VET teachers navigate the sometimes-conflicting educational goals of employability and civic engagement, while simultaneously teaching a highly diverse group of students. In both countries, pedagogic practices are dominated by individualisation with a focus on task-related skills. Those practices are important in VET, but can exclude broader understandings of civil and workplace life, because general knowledge about areas such as ethics, democracy, equality, and environmental issues is difficult to obtain if education gives students few opportunities to interact with others, such as through group work or classroom discussions.